2002
DOI: 10.1002/1521-3951(200211)234:2<689::aid-pssb689>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Defect Creation under UV Irradiation of CsI:Pb Crystals in Pb2+-Induced Absorption Bands Investigated by Luminescence Methods

Abstract: The creation of defects in CsI:Pb crystals by ultraviolet radiation at 4.2 K has been investigated by thermally stimulated and optically stimulated luminescence methods. The origin of the optically created defects has been established. The dependences of the defect creation efficiency on the irradiation energy and time, on the uniaxial stress, and on the concentration of the impurity (Pb 2+ and Na + ) ions have been found. The charge-transfer processes taking place under irradiation of CsI : Pb crystals in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
(22 reference statements)
1
3
0
Order By: Relevance
“…We assume that the 2.6 eV emission of LuAG:Bi arises from the radiative decay of an exciton localized near a Bi 3+ ion (see also [11]). A similar interpretation was proposed for the well-known visible luminescence of a CsI:Tl scintillator [30,31] and also of some other Tl + -and Pb 2+doped cesium halides (see, e.g., [31][32][33][34] and references therein), as well as for Pb 2+ -doped CdCl 2 crystals [35]. Indeed, the large values of the Stokes shifts and FWHM, as well as the low-temperature luminescence decay kinetics, namely relatively short (∼10 −5 s) decay times at 4.2 K and especially their temperature dependences, pointing to a very small (∼10 −4 eV) spin-orbit splitting energy of the triplet RES as compared with that in a Bi 3+ ion (∼10 −1 eV), are also characteristic for the radiative decay of the triplet exciton state.…”
Section: Visible Luminescencesupporting
confidence: 73%
See 1 more Smart Citation
“…We assume that the 2.6 eV emission of LuAG:Bi arises from the radiative decay of an exciton localized near a Bi 3+ ion (see also [11]). A similar interpretation was proposed for the well-known visible luminescence of a CsI:Tl scintillator [30,31] and also of some other Tl + -and Pb 2+doped cesium halides (see, e.g., [31][32][33][34] and references therein), as well as for Pb 2+ -doped CdCl 2 crystals [35]. Indeed, the large values of the Stokes shifts and FWHM, as well as the low-temperature luminescence decay kinetics, namely relatively short (∼10 −5 s) decay times at 4.2 K and especially their temperature dependences, pointing to a very small (∼10 −4 eV) spin-orbit splitting energy of the triplet RES as compared with that in a Bi 3+ ion (∼10 −1 eV), are also characteristic for the radiative decay of the triplet exciton state.…”
Section: Visible Luminescencesupporting
confidence: 73%
“…The processes of the localized exciton states creation under excitation in the impurity-induced absorption bands have been considered in detail for CsI:Tl [32] and CsI:Pb [33] crystals. It was suggested that, under excitation in the impurityinduced absorption bands, an electron transfer occurs from a halogen ion to an impurity ion, resulting in the creation of an electron impurity center and a self-trapped hole.…”
Section: Visible Luminescencementioning
confidence: 99%
“…The appearance of the STE luminescence under excitation in the Eu 2+ -related absorption region can be explained in a similar way as it was done in [13][14][15] for the Tl + -and Pb 2+ -doped cesium halides. We assume that under excitation in the 4.1-5.7 eV energy range, electron transfer from the 5p orbital of an I − ion, perturbed by a close Eu 2+ ion, to a vacant 6s orbital of the Eu 2+ ion takes place.…”
Section: Papermentioning
confidence: 72%
“…However, in the case of non-ionizing UV irradiation with the photon energy much smaller than the energy gap, the mechanism of defect creation is not clear. In [13][14][15], the creation of defects in Tl +and Pb 2+ -doped caesium halides by photons of energies, which are up to 2.5 eV smaller than the band gap energy, was explained by the charge-transfer process resulting in the appearance of free electrons and mobile holes in the crystal lattice. In these crystals, containing effective traps for electrons, the optically created electrons are trapped by impurity ions and the holes are self-trapped.…”
Section: Introductionmentioning
confidence: 99%